Lesion locations influencing baseline severity and early recovery in ischaemic stroke. (22nd May 2014) - Bentley, P.; Kumar, G.; Rinne, P.; Buddha, S.; Kallingal, J.; Hookway, C.; Sharma, P.; Mehta, A.; Beckmann, C.
<x xml:space="preserve">Abstract</x> Background and purpose Strokes caused by lesions to certain brain areas are associated with poor outcome, which is important both prognostically and to understand the neural basis for recovery. However, lesion anatomy associations with outcome may occur because of effects on baseline severity rather than because of effects on recovery per se. Here, all common stroke locations were surveyed to determine the strongest lesion anatomy associations separately for baseline functional severity and proportional recovery. Since most recovery occurs early, the focus here is on functional changes over the first week. Method Global functional scores (National Institutes of Health Stroke Scale) at baseline and proportional recovery over 1 week were derived from the records of 550 ischaemic stroke patients and related to magnetic resonance imaging lesion location using voxel‐lesion mapping. The effects of lesions extending over more than one location were also considered. Cross‐validation estimated the percentage of recovery rate variance (r2) accountable by lesion location information. Results High baseline severity was associated with lesions to the left capsule, striatum and thalamocortical white matter, whereas high recovery rate was associated with lesions to more superficial left fronto‐temporal areas. Low recovery rates were associated with lesions to bilateral parietal, right insula, medial frontal, capsule and brainstem. Inclusion of these regions into a multivariate model of proportional recovery rate increased r2 from 8% to 45%. Conclusion The strongest stroke lesion location associations with 1‐week recovery were identified, and it was shown that anatomical information accounts for a sizeable proportion of early recovery variability.